Algorithm for the torque sensorless worm gearbox servo application based on kinetic motion/friction realization. (August 2021) - Homaeinezhad, Mohammad Reza; Adineh, Shayan
This paper provides an effective systematic procedure for the efficient treatment of worm gearboxes for industrial-grade cases. The accurate and general dynamic model of the worm gearbox is analytically obtained and the effects of the dominant factors, such as the disturbance torque and friction between the teeth and threads, are also addressed. A universal algorithm is proposed for accurate estimation of the disturbance torque that makes no utilization of any designated sensing unit. Numerous experimentations have been conducted to validate the proposed procedure and algorithm. The contributions of this paper are not limited to worm gearboxes but rather are extendable to all other conventional gearboxes that use similar power transmission methods. The gradient patterns of the normal force, the friction force, and the coefficient of friction in worm gearboxes are also identified as a function of the effective elements, such as the output loading torque and angular velocity.